Using the Response Surface Method (RSM) for 2^k Factorial Design in Process Improvement and Optimization with Application to Al-Fataeh Cement Factory in Derna City - Libya - Miaad Fadhel Aliwi,; Obaid Mahmoud Al-Zubaie, (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
Research study and analysis of the question of improving the production processes and optimize the production of cement that is considered important and vital industries in the economy of a State. Through the use of modern statistical methods in quality control of production processes in order to identify deviations in the productive process and structure appropriate corrective action in time. Response surface method was used in optimizing factorial design 2k on improving compressive strength of cement by examining the effect of the four phases in clinker cement product , as the results showed that the phases and , have the greatest impact in improving the strength of cement resistance at high levels to each of them, also the results showed that the optimization process is recognized when the focus (36) for the first phase and the concentration (67) for the second one when the power of resistance to compression is (27.75).